Expression, characterization, and immobilization of a novel SGNH esterase Est882 and its potential for pyrethroid degradation - Zong, Wei; Su, Wenfeng; Xie, Qingfen; Gu, Quliang; Deng, Xinyi; Ren, Yifei; Li, He (Frontiers in Microbiology, 2022)
The widely-used pyrethroid pesticides have attracted public attention because of their potentials to cause environmental pollution and toxic effects on non-target organisms. Esterase is a kind of hydrolytic enzyme that can catalyze the cleavage or formation of ester bonds. it plays a pivotal role in the decomposition of pyrethroids and esters containing industrial pollutants through the hydrolysis of ester bonds. Here a new esterase gene est882 was successfully screened, which encodes Est882, a SGNH family esterase composed of 294 amino acids. It was heterogeneously expressed, identified and immobilized. Multiple sequence alignment showed that Est882 had a typical GDS(X) conserved motif and a catalytic triad composed of Ser79, Asp269 and His275. Phylogenetic analysis showed that Est882 shall belong to a new esterase family. Biochemical characterization demonstrated that the optimum condition was 40ºC and pH 9.0. Est882 immobilization was studied with mesoporous silica SBA-15 as the carrier and found to significantly improved the tolerance and stability of Est882. Its optimum pH increased to 10.0 and stabilized within pH 8.0-11.0. Free Est882 can effectively degrade various pyrethroids within 30 min, with a degradation rate above 80%. The immobilized Est882 yet degraded more than 70% of pyrethroids within 30 min. The present study indicated that Est882 has outstanding potential in bioremediation of a pyrethroid-polluted environment. These characteristics endow Est882 with potential values in various industrial applications and hydrolysis of pyrethroid residues.